2000
DOI: 10.1023/a:1004132414511
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The sexual isolation among the related species Drosophila melanogaster, D. simulans and D. mauritiana is asymmetrical. While D. mauritiana males mate well with both D. melanogaster and D. simulans females, females of D. mauritiana discriminate strongly against males of these two species. Similarly, D. simulans males mate with D. melanogaster females but the reciprocal cross is difficult. Interspecific crosses between several populations of the three species were performed to determine if (i) males and females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These efforts have yielded maps that vary in refinement from whole chromosomes, chromosomal arms, subchromosomal regions, to specific QTLs. Although the genetic basis of female discrimination may be species pair specific [135], one common attribute of these loci is their location in the genome: most of these loci fall within areas of low recombination, such as species inversion polymorphisms, regions near the centromere, and regions near the telomere. Behavioral isolation loci between D. santomea and D. yakuba were found near the centromere on 3R [7], and near the telomere for both the D. simulans and D. mauritiana species pair [6] and the M and Z forms of D. melanogaster [92].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These efforts have yielded maps that vary in refinement from whole chromosomes, chromosomal arms, subchromosomal regions, to specific QTLs. Although the genetic basis of female discrimination may be species pair specific [135], one common attribute of these loci is their location in the genome: most of these loci fall within areas of low recombination, such as species inversion polymorphisms, regions near the centromere, and regions near the telomere. Behavioral isolation loci between D. santomea and D. yakuba were found near the centromere on 3R [7], and near the telomere for both the D. simulans and D. mauritiana species pair [6] and the M and Z forms of D. melanogaster [92].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether there is genetic variation for D. simulans female preference, different lab strains of D. simulans females [86, 135] and D. melanogaster males [86] were compared for their rate of interspecific mating. Crossability, the ability for the parental strains or species to successfully produce offspring, varied among strains for both D. melanogaster males and D. simulans females [86, 87], but were still highly correlated [135].…”
Section: Genetic Basis Of Female Behavioral Isolation For Differenmentioning
confidence: 99%
See 1 more Smart Citation
“…The Drosophila genus has multiple closely related species that are sexually isolated, making it a commonly used model for studying behavioural isolation [14,20]. Drosophila melanogaster and D. simulans are two species that are behaviourally isolated: while D. melanogaster females mate at high frequencies with D. melanogaster males, D. simulans females do not [21,22]. However, hybrid females from the permissive cross between D. melanogaster females and D. simulans males [23,24] will mate with D. melanogaster males [25].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, D. melanogaster females do not display this similar discrimination in mating behaviour and accept courtship and copulate with D. simulans males. 12 We are currently working to isolate potential mate preference loci within the tip of the right arm of the third chromosome which previous research has indicated is a region encoding female mate preference in Drosophila.…”
Section: The Study Of Drosophila Mate Preference As a Research Assistmentioning
confidence: 99%